2016
DOI: 10.1176/appi.neuropsych.15100241
|View full text |Cite
|
Sign up to set email alerts
|

Apathy Is Associated With Ventral Striatum Volume in Schizophrenia Spectrum Disorder

Abstract: Apathy is prevalent in schizophrenia, but its etiology has received little investigation. The ventral striatum (VS), a key brain region involved in motivated behavior, has been implicated in studies of apathy. We therefore evaluated whether apathy is associated with volume of the VS on MRI in 23 patients with schizophrenia using voxel-based morphometry. Results indicated that greater self-reported apathy severity was associated with smaller volume of the right VS even when controlling for age, gender, depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 45 publications
5
19
5
Order By: Relevance
“…This relationship persisted after considering several a priori variables often associated with amotivation and brain morphology. These findings are consistent with the theorized role of the VS in motivation and replicate and extend previous findings . Controlling for age, gender, depression (Beck Depression Inventory II scores), and total GM, Roth and colleagues found that amotivation, measured with the Apathy Evaluation Scale, was associated with smaller right VS volumes in schizophrenia patients.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…This relationship persisted after considering several a priori variables often associated with amotivation and brain morphology. These findings are consistent with the theorized role of the VS in motivation and replicate and extend previous findings . Controlling for age, gender, depression (Beck Depression Inventory II scores), and total GM, Roth and colleagues found that amotivation, measured with the Apathy Evaluation Scale, was associated with smaller right VS volumes in schizophrenia patients.…”
Section: Discussionsupporting
confidence: 86%
“…These findings are consistent with the theorized role of the VS in motivation 16 and replicate and extend previous findings. 14 methods and a different measure of amotivation, we replicate these findings while additionally controlling for general positive symptoms and estimated antipsychotic D 2/3 R occupancy. Thus, our data suggest that amotivation is uniquely associated with reduced VS volumes, above and beyond striatal D 2/3 R blockade by antipsychotics.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations